Seals and walruses - Barrett, Norman S. (New York : F. Watts, 1991)
Depicts the habitat, feeding habits, and life cycle of seals and walruses.
Includes index.
6.6
3-5.
3-6
Keywords: Seals (Animals) -- Juvenile literature; Walruses -- Juvenile literature; Seals (Animals); Walruses; Seals (Animals); Walruses